1981
DOI: 10.1159/000123121
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation between Hypothalamic Serotonin and the Ether-Induced ACTH Secretion in Adrenalectomized Rats

Abstract: The central serotonergic system was manipulated using a serotonin receptor antagonist (cyproheptadine), electrolytic lesioning of the raphe nuclei and neurochemical destruction of the serotonergic terminals in the hypothalamus. The effects of these interventions on ether-induced ACTH secretion were studied in adrenalectomized rats. Serotonin, norepinephrine and dopamine concentrations were measured in the medial basal hypothalamus (MBH) or in individual nuclei of the hypothalamus and of certain midbrain region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…and concomitant decrease in plasma GH observed within 5 15 min after exposure to ether vapors in the present study agree with previous reports demonstrating stress-induced alterations in the levels of ACTH [12,32], PRL [19], |5-F.nd [7,18], and GH [32], They also provide new evidence indi cating selective and differential changes in monoamine me tabolism in stressed animals within the various discrete brain areas.…”
Section: Discussionsupporting
confidence: 93%
“…and concomitant decrease in plasma GH observed within 5 15 min after exposure to ether vapors in the present study agree with previous reports demonstrating stress-induced alterations in the levels of ACTH [12,32], PRL [19], |5-F.nd [7,18], and GH [32], They also provide new evidence indi cating selective and differential changes in monoamine me tabolism in stressed animals within the various discrete brain areas.…”
Section: Discussionsupporting
confidence: 93%
“…Other lesion studies by Szafarczyk et al [45] indicate that 5-HT terminals outside the SCN are also involved in generating the diurnal rhythm in ACTH release. Ganong [16], however, finding no effect of injecting low doses of L-tryptophan on plasma corticosteroids in the'dog, suggests that 5-HT systems may not affect ACTH release, and others have reached a similar conclusion [23,25,36]. On the other hand, Fuller [ 13] and Fuller el al.…”
Section: Discussionmentioning
confidence: 98%
“…Several experiments have failed to find a supporting role for 5-HT in pituitary adrenal control (Dixit and Buckley, 1969;Berger et al, 1974;Pavel et al, 1977;Karteszi et al, 1981), but many pharmacological studies have found a stimulatory role for 5-HT in ACTH regulation.…”
mentioning
confidence: 99%
“…Jones et al (1976) demonstrated that 5-HT stimulated CRF release from rat hypothalami in in vitro experiments, but few studies (Karteszi et al, 1981) have examined the effects of these compounds on CRF activity in the hypothalamus employing in vivo methods.…”
mentioning
confidence: 99%